2016
DOI: 10.1108/ijppm-11-2014-0182
|View full text |Cite
|
Sign up to set email alerts
|

After 20 years, what has remained of TQM?

Abstract: Purpose – Many Brazilian organizations have adopted total quality management (TQM). However, this model has lost prominence in academic and business environments. The purpose of this paper is to determine which aspects of TQM have endured over 20 years. Design/methodology/approach – With descriptive and exploratory objectives, this study used case studies of four companies that have adopted TQM, using temporal and comparative approaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…As a whole, these findings suggest that, while the TQM concept has persisted (Venkateswarlu and Nilakant 2005), there is much variation in terms of implementation patterns. Therefore, it is still, to a large extent an open question precisely what parts of the TQM concept have persisted in practice (Bernardino et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…As a whole, these findings suggest that, while the TQM concept has persisted (Venkateswarlu and Nilakant 2005), there is much variation in terms of implementation patterns. Therefore, it is still, to a large extent an open question precisely what parts of the TQM concept have persisted in practice (Bernardino et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Case study Bernardino et al (2016) The appropriation of the TQM model was more widespread in the management area. However, what should in principle be to improve the system, created more demand for records and notes that caused a loss of focus on problems.…”
Section: Methodsmentioning
confidence: 99%
“…Case study Moreira and Cheng (2010) Source: Own Authorship From the bibliographic search, it is perceived organizations that implemented several quality tools, seeking a management that established meaningful communication with suppliers (Silva et al, 2019), and in addition organizations that seek contact with employees to improve informal internal communication and achieve "quality teams", going in confrontation with the traditional behavior of management models (Bernardino et al, 2016). However, it shows that the changes in the internal coordination system were not structured with the same efficiency, since only three studies demonstrated organizations with well-established goals in the various functions, obtaining a high administration committed to the TQM plan (Silva et al, 2019;Bernardino et al, 2016;Berssaneti et al,2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Portanto, parte-se do pressuposto que a proposta de um modelo para gestão de repositórios deve estar acompanhada de estratégias para melhoria contínua dos processos, nos moldes do que podemos encontrar em outras áreas do conhecimento, como em processos de manufatura nas Engenharias e na própria abordagem da Gestão da Qualidade (BERNARDINO et al, 2016).…”
Section: Introductionunclassified